Hepatoprotective effects of safranal on acetaminophen-induced hepatotoxicity in rats - Alayunt, Naci Omer; Parlak, Akif Evren; Turkoglu, Semra; Tas, Fatih (De Gruyter Poland Sp Z O O, 2024)
This research aimed to explore the protective and therapeutic properties of safranal in mitigating inflammation and oxidative stress induced by elevated acetaminophen (APAP) doses in a rat model. The protective and therapeutic effects of safranal were determined by histopathologically and examining some biochemical parameters such as aspartate transaminase (AST), alanine transaminase (ALT), glutathione, glutathione peroxidase, catalase, malondialdehyde, interleukin-6, tumor necrosis factor-alpha, and interleukin-1 beta. Male Wistar-Albino rats were subject to random allocation, forming five groups, each comprising seven rats (n = 7) in the study. Group 1 was the control group. APAP was administered in Group 2 to induce hepatotoxicity. Rats in Groups 3, 4, and 5 received intraperitoneal injections of safranal at doses of 0.025, 0.05, and 0.1 mL/kg/day for 14 days, respectively. On the 15th day, to induce APAP-induced hepatotoxicity, four groups (Groups 2, 3, 4, and 5) acquired a single intraperitoneal injection of 600 mg/kg APAP. The presence of APAP-induced hepatotoxic effect was proven by elevated AST and ALT levels, which are typical biomarkers of liver function in addition to the demonstration of histopathological changes. The findings suggest that pre-treatment with safranal may offer a protective effect against hepatotoxicity by attenuating oxidative stress and the inflammatory response.
Keywords: antioxidant; inflammation; liver injury; oxidative stress; safranal